Magnetron with a concave hemispherical cathode - Stetsenko, B.V.; Shchurenko, A.I.; Zavyalov, Yu.G. (Вопросы атомной науки и техники, 2009)
A magnetron set up with a hemispherical concave cathode has been worked out for the first time. The cathode center of curvature was registered with the sputtered surface. An aluminum nitride film was sputtered by this magnetron in the pulse regime. The pulse duration was about 2 ms. The film thickness was between 10 to 12 nm. The sputtering rate was about 50 nm/s. The magnetron characteristics agree with a qualitative model of the magnetron.